10 steps to successful facilitation (10 steps., 2018)
Facilitate Groups That Deliver Results Every professional businessperson needs a complete portfolio of skills, yet one area is often taken for granted: the art of facilitation. This book takes the guesswork out of this essential skill and gives you a step-by-step process for becoming an accomplished and successful facilitator. As a facilitator, your job is to remain neutral while helping others achieve common objectives. To do this, you need tools and techniques to deal with a wide variety of group meeting situations. In 10 Steps to Successful Facilitation, you'll find everything you need, including A wealth of methods and ideas to engage participants Strategies for handling conflict and creating a collaborative climate Tips for using media and technology effectively This second edition features updates to each step, reorganized to align with the problems facilitators face today, such as the increasing prevalence of virtual meetings. You'll have the help you need to act as a catalyst for progress, enabling others to focus on key issues, arrive at appropriate solutions, and build sustainable agreements. With this book as your roadmap, you can be thoroughly prepared for the role of facilitator, ready to cultivate cooperation and understanding among individuals and assist your organization in developing shared solutions to its challenges.